Sharia Literacy as Social Capital: A Comparative Study between Indonesia and Other Muslim Countries - Rido Hermawan; Kup Yanto Setiyono; Caturida Meiwanto Doktoralina; Inna Vladimirovna Lukashenko; Lucky Nugroho (Economics & Islamic Finance Journal (ECIF), 2025)
Without appropriate sharia literacy, the Muslims living in Muslim majority countries have not been able to be part of the Islamic finance movement led by these institutions. This paper discusses sharia literacy as social capital to boost Islamic financial inclusion: a case of Indonesia and comparative perspective of Malaysia, Türkiye, Pakistan and Bangladesh. Using a structured narrative literature review, the study follows qualitative descriptive approach and reviews literature on Islamic financial literacy, social capital theory, financial inclusion, digital literacy and normative underpinnings of Islamic economics. Results indicate that sharia literacy incorporating both the technical and moral-spiritual aspects of sharia  sustains collective norms, cultivates a trust in institutions, and fosters participation in voluntary systems of sharia-complaint finance. Islamic social capital plays a vital role in increasing financial inclusion, whereas digital literacy helps to widen access. Indonesia’s gap, of a literacy index 39.11% and an inclusion rate of just 12.88% in 2023, shows not an absence of Islamic social foundations but the difficulty in processes of converting literacy to sustained financial behaviour. Utilising maqāṣid al-sharī'ah-based frameworks within financial education and policy is a strategic approach with the potential to reshape financial literacy levels in the Islamic financial ecosystem.